2015
DOI: 10.1186/s12995-015-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

Hospital physicians’ work stressors in different medical specialities: a statistical group comparison

Abstract: BackgroundSome studies on the occupational health of hospital physicians have found that working conditions have different effects on physician’s well-being and health in different medical specialities. There has been no comparative study of the effects of various work stressors in different specialities. This study aims to close this gap.MethodsGerman hospital physicians were asked about their working conditions and aspects of health. The short version of the Instrument for Stress-Related Job Analysis for Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…The process of losing physicians from public teaching hospitals typically begins after graduation. Among the publications studied [42, 43, 4547, 4951], there is no unanimity with regard to the factors that affect turnover, with aspects such as age, specialty, and post-graduation studies having been identified. However, there is a trend to agree that the more specialized physicians tend to remain in higher-complexity services.…”
Section: Discussionmentioning
confidence: 99%
“…The process of losing physicians from public teaching hospitals typically begins after graduation. Among the publications studied [42, 43, 4547, 4951], there is no unanimity with regard to the factors that affect turnover, with aspects such as age, specialty, and post-graduation studies having been identified. However, there is a trend to agree that the more specialized physicians tend to remain in higher-complexity services.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, however, that lack of time for direct patient contact is a major cause of job dissatisfaction for hospital doctors (27,28). Especially dissatisfaction with the burden of administrative tasks and documentation is an important contributor to work-related stress and emotional exhaustion (29). Furthermore, hospital patients subjectively place a high value on physicians having sufficient time for ward rounds and personal discussions, but are often dissatisfied with the amount of time dedicated to them (30).…”
Section: Discussionmentioning
confidence: 99%
“…Stressors are characteristics that increase the probability of stress outcomes and have different effects in a variety of medical specialities. 38 We should evaluate and explore the main stressors in anaesthesiologists to be able to better reduce negative stress consequences in personal and professional lives. 2,14 The SQA is a questionnaire that measures specific stressors and can be used to identify problems in the working conditions of anaesthesia physicians to encourage and improve the development of 'wellness'.…”
Section: Discussionmentioning
confidence: 99%